2007
DOI: 10.1002/art.23049
|View full text |Cite
|
Sign up to set email alerts
|

Arthritogenic antibodies specific for a major type II collagen triple‐helical epitope bind and destabilize cartilage independent of inflammation

Abstract: Objective. To investigate the significance and pathogenic potential of a highly conserved major type II collagen triple-helical epitope-specific antibody (U1; amino acids 494-504) in vivo and in vitro in patients with early rheumatoid arthritis (RA) and in experimental animal models of collagen-induced arthritis (CIA).Methods. U1-specific antibodies in sera from patients with early RA (with or without joint erosions) were analyzed. Disease progression in the CIA models in mice and rats with anti-U1 antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
74
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 49 publications
4
74
1
Order By: Relevance
“…Collagen I is one of the major components of periodontal tissues (31) and, it was shown, mainly for RA, that Abs binding to self-Ags can initiate an inflammatory reaction in tissues, possibly through the release of tissue-degrading enzymes (32) and cytokines (33) by the infiltrating cells (34). In this study, the production of proinflammatory cytokines, such as TNF-a and IL-17, was enhanced by cells of AIA mice when stimulated by collagen I.…”
Section: Discussionmentioning
confidence: 53%
“…Collagen I is one of the major components of periodontal tissues (31) and, it was shown, mainly for RA, that Abs binding to self-Ags can initiate an inflammatory reaction in tissues, possibly through the release of tissue-degrading enzymes (32) and cytokines (33) by the infiltrating cells (34). In this study, the production of proinflammatory cytokines, such as TNF-a and IL-17, was enhanced by cells of AIA mice when stimulated by collagen I.…”
Section: Discussionmentioning
confidence: 53%
“…Anti-CII antibodies are believed to be arthritogenic in murine CIA; in fact, transfer of serum containing these antibodies can induce arthritis in healthy animals (16,18,21). Bovine or rat CII used to immunize animals in the CIA model elicits an antibody response specific for CII.…”
Section: Resultsmentioning
confidence: 99%
“…Bovine or rat CII used to immunize animals in the CIA model elicits an antibody response specific for CII. These antibodies against foreign collagen are believed to cross-react with self collagen and become pathogenic (21,33). In the model of arthritis developed in this study, we demonstrated the breach of self tolerance toward collagen and the production of anti-CII and anti-U1 antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations